STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN KERAPU SISTEM KERAMBA JARING APUNG DI TELUK AMBON DALAM - Irawati Irawati; Muhidin Syamsuddin (Jurnal Akuakultur Sungai dan Danau, 2020)
The development of grouper aquaculture production in the waters of Teluk Ambon Dalam (TAD) has increased from year to year, both in the amount of production, aquaculture household and the area of cultivation land. This indicates that the community is increasingly reading the opportunities for grouper farming in Ambon Dalam Bay. Increased production of course must be followed by certainty of market availability, because the success or failure of a cultivation business is determined by market conditions. On this basis, the research entitled "Strategy of Grouper Cultivation Cultivation Business System of Floating Nets in Ambon Dalam Bay" was conducted. The subject of this research is the community of systema grouper fish farming floating net cages at the location of Teluk Ambon Dalam, Baguala District, Ambon City. The components of the research analyzed were the conditions of the grouper cultivation business which were analyzed using descriptive qualitative methods; the marketing system is analyzed using the marketing system analysis method; Business feasibility was analyzed using business feasibility analysis method and internal and external components were analyzed using the SWOT and TOWS methods. The results showed that the condition of Ambon Dalam Bay waters quality still supports the development of grouper cultivation activities. For domestic marketing of grouper fish in Ambon City, the marketing channels are producer-buyer / collector-consumer. From the marketing channels formed above, it can be said that, this marketing channel is included in the two-tier marketing channel. The results of the business feasibility analysis indicated that the grouper farming was feasible to continue. Formulated 15 strategies for developing marketing of grouper farming in the waters of Teluk Ambon Dalam (TAD).